2023
DOI: 10.3389/fmicb.2023.1143265
|View full text |Cite
|
Sign up to set email alerts
|

Screening and characterization of Bacillus velezensis LB-Y-1 toward selection as a potential probiotic for poultry with multi-enzyme production property

Abstract: Bacillus spp. have gained increasing recognition as an option to use as antimicrobial growth promoters, which are characterized by producing various enzymes and antimicrobial compounds. The present study was undertaken to screen and evaluate a Bacillus strain with the multi-enzyme production property for poultry production. LB-Y-1, screened from the intestines of healthy animals, was revealed to be a Bacillus velezensis by the morphological, biochemical, and molecular characterization. The strain was screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…These findings suggest that Bacillus velezensis TS5 has the potential to promote nutrient digestion. A study indicated that the cellulase and phytase secreted by Bacillus velezensis LB-Y-1 contribute to the release of nutrients in Arbor Acres broiler chickens feed ( Li et al, 2023 ). The protease and amylase secreted by Bacillus velezensis LB-Y-1 enhanced the intestinal digestibility of broilers, thereby promoting nutrient digestion.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that Bacillus velezensis TS5 has the potential to promote nutrient digestion. A study indicated that the cellulase and phytase secreted by Bacillus velezensis LB-Y-1 contribute to the release of nutrients in Arbor Acres broiler chickens feed ( Li et al, 2023 ). The protease and amylase secreted by Bacillus velezensis LB-Y-1 enhanced the intestinal digestibility of broilers, thereby promoting nutrient digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen different local breeds of chickens were slaughtered in various regions of China. Broiler cecum was isolated and preserved at −20 • C. Bacillus strain was isolated using the method previously described with minor modifications [12]. The cecal contents were homogenized with phosphate-buffered saline at 1:9 (w/v) ratio, and the compound was then heated in an 80 • C water bath for 10 min.…”
Section: Sample Collection Isolation and Identification Of Bacillus S...mentioning
confidence: 99%
“…B. velezensis ZBG17 isolated from soil samples enhanced feed utilization efficiency and heightened the humoral immune response in broiler chickens [11]. Similarly, B. velezensis LB-Y-1 obtained from the digestive tracts of freeranging animals promoted broiler chickens' growth performance and the mineralization of tibias by enhancing the activities of intestinal digestive enzymes, increasing phosphorus metabolism and utilization, and altering the intestinal microbiota [12]. B. velezensis isolated from piglet manure has been shown to improve the laying hens' egg production and quality, as well as plasma biochemical indicators [13].…”
Section: Introductionmentioning
confidence: 97%
“…It is well established that this Bacillus strain has the capacity to generate diverse enzymes, including protease, cellulase, amylase, and glucanase. Additionally, it secretes antibacterial substances, effectively inhibiting the growth of pathogenic microorganisms [64,65]. Gui et al discovered a deep-sea B. velezensis with the ability to break down waterborne polyurethane [66].…”
Section: Sample 5: Soil Contaminated With Biopolymersmentioning
confidence: 99%